2008
DOI: 10.1038/jhh.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation in hypertension prevalence of women in Taiwan

Abstract: The prevalence and risk factors of hypertension vary in ethnic groups. This study aimed to estimate the hypertension prevalence and to compare risk factors associated with hypertension in women of four ethnic groups in Taiwan. The study subjects were participants in the Taiwanese Survey on Hypertension, Hyperglycemia and Hyperlipidemia (TwSHHH) enrolled in 2002. In this analysis, only 2810 women who were at age of 20-80 years old and whose father and mother had same ethnic background (Minnan, Hakka, Aborigines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indeed, minorityemajority disparities in both high-risk behaviors and in health outcomes are remarkably common, despite differences in the genetic background of different non-dominant minority groups, and the heterogeneous historical contexts and events that led to their marginalization (e.g., through enslavement, colonization, or immigration). Thus, similar patterns can be observed in Maori New Zealanders vs. "pakeha" New Zealanders of European descent (Edwards et al, 2009); Australian Aborigines vs. white Australians (Guest, O'Dea, Carlin, & Larkins, 1992); First Nations tribes vs. the rest of Canada (Leslie, Weiler, & Nyomba, 2007;Oster & Toth, 2009); aboriginal Taiwanese vs. Chinese-ethnic Taiwanese from the mainland (Ho & Tsai, 2007;Su, Hwang, You, & Chen, 2009); Gypsies and Travelers vs. whites in England (Peters et al, 2009); Central and Eastern European migrants vs. the general population in London (Burns et al, 2011); individuals of Turkish vs. Dutch descent in the Netherlands (Ujcic-Voortman et al, 2010); non-Jews vs. Jews in Israel (Factor, Mahalel, & Yair, 2008;Factor, Yair, & Mahalel, 2010;Nitzan Kaluski, Demem Mazengia, Shimony, Goldsmith, & Berry, 2009); Native Americans vs. white Americans (Falk, Yi, & Hiller-Sturmhofel, 2006;Grossman, Sugarman, Fox, & Moran, 1997); and in African Americans (or blacks) vs. whites in the U.S. (Williams, Mohammed, Leavell, & Collins, 2010). Similar patterns can also be observed in groups of lower socioeconomic and educational status in the U.S. (Fujiwara & Kawachi, 2009;Phelan, Link, Diez-Roux, Kawachi, & Levin, 2004;Sorensen et al, 2004), and where socioeconomic status intersects with race (Braveman, Cubbin, Egerter, Williams, & Pamuk, 2010;Kawachi, Daniels, & Robinson, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, minorityemajority disparities in both high-risk behaviors and in health outcomes are remarkably common, despite differences in the genetic background of different non-dominant minority groups, and the heterogeneous historical contexts and events that led to their marginalization (e.g., through enslavement, colonization, or immigration). Thus, similar patterns can be observed in Maori New Zealanders vs. "pakeha" New Zealanders of European descent (Edwards et al, 2009); Australian Aborigines vs. white Australians (Guest, O'Dea, Carlin, & Larkins, 1992); First Nations tribes vs. the rest of Canada (Leslie, Weiler, & Nyomba, 2007;Oster & Toth, 2009); aboriginal Taiwanese vs. Chinese-ethnic Taiwanese from the mainland (Ho & Tsai, 2007;Su, Hwang, You, & Chen, 2009); Gypsies and Travelers vs. whites in England (Peters et al, 2009); Central and Eastern European migrants vs. the general population in London (Burns et al, 2011); individuals of Turkish vs. Dutch descent in the Netherlands (Ujcic-Voortman et al, 2010); non-Jews vs. Jews in Israel (Factor, Mahalel, & Yair, 2008;Factor, Yair, & Mahalel, 2010;Nitzan Kaluski, Demem Mazengia, Shimony, Goldsmith, & Berry, 2009); Native Americans vs. white Americans (Falk, Yi, & Hiller-Sturmhofel, 2006;Grossman, Sugarman, Fox, & Moran, 1997); and in African Americans (or blacks) vs. whites in the U.S. (Williams, Mohammed, Leavell, & Collins, 2010). Similar patterns can also be observed in groups of lower socioeconomic and educational status in the U.S. (Fujiwara & Kawachi, 2009;Phelan, Link, Diez-Roux, Kawachi, & Levin, 2004;Sorensen et al, 2004), and where socioeconomic status intersects with race (Braveman, Cubbin, Egerter, Williams, & Pamuk, 2010;Kawachi, Daniels, & Robinson, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…However, the life expectancy of Taiwanese aborigines was nine years fewer than that of non‐aboriginal people, according to the statistics released by Taiwan Ministry of the Interior in 2010. An epidemiology survey in 2009 also confirmed that Taiwanese aborigines had the highest prevalence of diabetes mellitus(8.9%) among different ethnic groups . Moreover, diabetes complications and extremely high blood sugar levels were frequently seen among Taiwanese aboriginal patients in our daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertensive crises are characterized by severely elevated blood pressure (BP), usually higher than 180/110 mmHg, along with progressive or impending target organ damage 17 . The ethnic composition of our cohort reflected a typical Taiwanese population 18 .…”
Section: Methodsmentioning
confidence: 99%